PENGARUH TINGKAT KEMATANGAN KOMPOS TANDAN KOSONG SAWIT DAN MULSA LIMBAH PADAT KELAPA SAWIT TERHADAP PRODUKSI TANAMAN TOMAT (Lycopersicon esculentum Mill.) PADA TANAH ULTISOL - Mercy Bientri Yunindanova; Herdhata Agusta; Dwi Asmono (Faculty of Agriculture, Universitas Sebelas Maret, 2013)
Title : The Effect of Maturity Level of Empty Fruit Bunch Compost and Mulch from Palm Oil Waste to Tomato Productivity in Ultisol. This research was conducted to understand the effect of maturity level of empty fruit bunch compost and mulch from palm oil waste to tomato productivity in ultisol soil. This research used split plot design with mulch as main plot and maturity level of compost as sub plot. The mulch consists of four types: control, shell, fiber, and chopped of empty fruit bunch. The maturity level of compost consists of 5 levels: control, 4 weeks, 6 weeks, 8 weeks, and 10 weeks. Material used in this research was tomato Ratna variety. Compost of 8 weeks gave the lowest value of C/N ratio (35.16) than 4, 6, and 10 weeks. This compost also had the highest level of N-total, P and Mg: 1.34 %, 0.08 %, and 0.25 %. Compost containing the lowest C/N ratio and higher nutrition gave better vegetative growt. Compost of 8 weeks and fiber mulch provided the highest harvest weight and the highest number of fruit (436.56 gram and 16 fruits). Fruit number and fruit weight were lower than general tomato cultivation because of soil condition. Soil type was ultisol which had lower acidity level. The lower KTK level of this soil made distruption in nutrients uptake. Compost of 8 weeks could increase harvest weight 52.59 % higher than control and also could raise number of fruit 82.53 % higher than control. Shell mulch presented negative effect to growth and productivity of tomato.